Pengaruh Penambahan High Fructose Corn Syrup terhadap Sifat Fisikokimia dan Sensoris Selai Edamame - Luhde, Ni Luh Gede Wiradani; Mayun Permana, I Dewa Gde; Kartika Pratiwi, I Desak Putu (Itepa : Jurnal Ilmu dan Teknologi Pangan, 2026)
Edamame jam is a jam made from edamame pulp with the addition of sugar, then cooked until thickened. The use of sand sugar in the processing of jam can result in a less smooth texture, making it difficult to apply to bread. A sand sugar concentration of more than 55% can result in crystallization of the jam after the heating process so that the resulting jam texture becomes hard. High Fructose Corn Syrup (HFCS) has a liquid texture so it is expected to be easier to process and at a certain concentration does not result in crystallization on the jam. The purpose of this study is to determine the effect of the addition of HFCS on the physiochemical and sensory properties of edamame jam and to obtain the right addition of HFCS in order to produce the best edamame jam characteristic. This research is an experimental study with a complete random design consisting of one factor, namely the concentration of HFCS addition of 25%, 30%, 35%, 40%, and 45%. All treatment was repeated 3 times so that 15 units of experiment were obtained. The data obtained is then analyzed using variance analysis and if there is an influence on the observed parameters, it will be continued with Duncan's Multiple Range Test. The results of the research showed that the concentration of HFCS in edamame jam had a significant influence (P<0,05) on moisture content, protein content, total sugar, antioxidant activity, total soluble solidity, viscosity, and sensory tests (hedonic and scoring). Edamame jam with the addition of 40% HFCS had the best jam characteristics with moisture content 23.68%, protein content 9.32%, total sugar 34.00%, antioxydant activity 10.98%, total solute solidity 60.10%brix, viskosity 35.06 Pa.s, spreadability 4.40 with criteria easy to spread, preferred color, aroma with preferred criteria, preferred sweet taste, preferred texture, and overall acceptance with preferred criteria that was acceptable to the panelists.